The Evolution of Ecological and Environmental Governance Attention Allocation in J City Based on Big Data Analysis - Jing Gao; Yuhan Sun (Discrete Dynamics in Nature and Society)
Analysing the evolution process of attention allocation in city governance is an effective way to understand modern governance. Among the city types, heavy industry cities are special cities. It relies too much on heavy industry and is difficult to achieve ecological and environmental governance. This study takes J City in Northeast China as an example. Based on big data analysis, this study analyses the evolution process of governance attention allocation in J City. It can be found that the realization of ecological and environmental governance requires people’s participation. City development needs multiple synergies and an ecosystem-led governance model. However, this process is not a subjective product but needs to be promoted by history. Fundamentally, people need to change the logic of economic development.